Transformasi Institut Agama Islam Negeri (IAIN) ke Universitas Islam Negeri (UIN) Sumatera Utara: Dinamika dan Tantangan, 2014-2020 - Utami, Dika Rahmayanti; Sumanti, Solihah Titin; Zuhriah, Zuhriah (Local History & Heritage, 2025)
This study examines the transformation dynamics of the State Institute for Islamic Studies (IAIN) of North Sumatra into the State Islamic University (UIN) of North Sumatra by highlighting its socio-historical context, institutional challenges, and strategic approaches. Employing a historical approach, the research investigates policy changes, the impact of globalization, and curriculum adaptation as integral components of the transformation process. The main research question focuses on how institutional strategies and contextual factors have shaped this transition. Findings suggest that the success of the transformation is closely linked to the implementation of strategic policies, enhancement of human resource capacity, and the institution's commitment to integrating religious sciences with general disciplines. The study concludes that this transition reflects not only an administrative upgrade but also a paradigm shift toward a more holistic educational model in response to both national reforms and global academic trends.